Spectrum of Severe Sepsis in Critically Ill Adult Patients of Bangladesh: A Prospective Observational study (Bangladesh Critical Care Journal, 2015)
Background: Severe sepsis is the leading cause to Intensive Care Unit (ICU) admission. However few studies have described the primary source of the severe sepsis in Bangladesh.Objectives: General objective was to identify the clinical presentation of infection in severe sepsis patients & specific objective was to determine the primary and commonest source of infection in severe sepsis.Methods: This was a prospective cross sectional study done over seven months period starting from June 1, 2012 to December 31, 2012 in the dept. of Critical Care Medicine of BIRDEM General Hospital. All ICU admissions from the emergency department, medical and surgical in patients who were screened daily for the presence of severe sepsis or septic shock using a screening tool, which included definitions of sepsis and organ dysfunctions. All consecutive patients with severe sepsis were enrolled as study subjects.Results: A total of 228 patients were admitted in ICU and among them, 95 patients of severe sepsis were included . The mean age of the patients was 59.56 years & male to female ratio being 3:2. Ninety two (92% ) patients had any kind of comorbidity. Commonest comorbidity was diabetes mellitus (77%). Respiratory, renal dysfunction, and cardiovascular, were the most frequent organ dysfunctions (87% , 64%, 58%, respectively). In severesepsis patients single organ dysfunction was 30 %, double organ dysfunction was also 30% & triple organ dysfunction was 35% of patients. The most common primary source of infection were the respiratory system 70%, followed by urinary tract11% , intravascular catheter related infection 7% and abdomen 5%.Conclusion: Severe sepsis is a significant & common health problem in ICU Patients of Bangladesh. An understanding of the primary sources of severe sepsis is vital for treatment and these information will allow us to make preventive strategy for severe sepsis.Bangladesh Crit Care J September 2015; 3 (2): 45-48